Increase the Strenght of Base and Subbase of Flexible Pavement by adding Fledspar as additive material - Gatot Rusbintardjo; Lisa Fitriyana; Nur Izzi M. Yusoff; Arafat Suleiman Yero (Universitas Islam Sultan Agung, 2019)
The strength and durability of the flexible pavement is highly dependent on the quality of the aggregate material used for base and subbase layers. This is can be understand since 95 percent of the weight-volume of the base and subbase layer is aggregate. Therefore using a good quality and strong base and subbase material is very important. In this paper, which is a report of a reseacrh, Feldspar is used as stabilizer of base and subbase materlias of flexible pavement. Feldspar is a group rock-ftant forming tectosilicate minerals that made up about 41% of the earth’s continental crust by weight. 5 to 25% of Feldspar with increment of 5% by weight of the base and also subbase were added. Direct Shear and California Baring Ratio (CBR) test were conducted., beside water content and dry density test. The results of direct shear test show that cohesion of base and subbase materials decrease from 0,164 kg/cm2 of original base and subbase materials become 0,01 kg/cm2 for base and subbase material after adding with 25% of Feldspar, and angle of inernal friction increase from 47,670 become 49,800. Meanwhile the results of CBR test show that CBR value of base increase from 30% to 86,40%, as well as for subbase increase from 21,50% to 87,30% after adding with 15% of Feldspar. It can be concluded that adding aggregate of base and subbase with Feldspar the strenght improve signicantly, and the influence is the strengthening of the base and subbase layers.